2019
DOI: 10.1128/mra.00273-19
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequences of Eight Canadian Citrobacter braakii and Citrobacter freundii Strains

Abstract: Citrobacter braakii and Citrobacter freundii are Gram-negative opportunistic pathogens associated with many infectious diseases, including septicemia, in humans and animals. Here, we report the draft genome sequences of seven C. braakii strains and one C. freundii strain isolated from Canadian wastewater treatment facilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…In addition, for the samples used in the current study, live coliforms, generic E. coli and Salmonella were detected for the biosolids collected in 2009 as described in a separate publication for which the WWTPs were named as WWTP A and C (Yergeau et al, 2016;Duceppe et al, 2019). Similar results for coliforms and generic E. coli have been obtained for the samples used in 2019 with the WWTPs referred as WWTP A and B respectively) (data not shown).…”
Section: Study Sites and Sample Collectionsupporting
confidence: 79%
See 2 more Smart Citations
“…In addition, for the samples used in the current study, live coliforms, generic E. coli and Salmonella were detected for the biosolids collected in 2009 as described in a separate publication for which the WWTPs were named as WWTP A and C (Yergeau et al, 2016;Duceppe et al, 2019). Similar results for coliforms and generic E. coli have been obtained for the samples used in 2019 with the WWTPs referred as WWTP A and B respectively) (data not shown).…”
Section: Study Sites and Sample Collectionsupporting
confidence: 79%
“…Several studies have shown the presence of live bacteria and ARBs in biosolids, indicating that treatments in WWTPs cannot completely inactivate all the bacteria (Alam et al, 2007;Viau and Peccia, 2009b;Yergeau et al, 2016). For the samples used in the current study, live coliforms, generic E. coli and Salmonella were detected for the biosolid samples collected in 2009 as described in separate publications for which the WWTPs were named as WWTP A and C (Yergeau et al, 2016;Duceppe et al, 2019). Similar results for coliform and generic E. coli have been obtained for the samples used in 2019 with the WWTPs referred as WWTP-A and -B respectively) (data not shown).…”
Section: Co-occurrence Patterns Between Args and Bacterial Communitiesmentioning
confidence: 71%
See 1 more Smart Citation
“…Citrobacter spp. with an average relative abundance of 1.45% maintained a low growth during storage, which have been considered as pathogen bacteria and associated with many diseases including septicemia in animals even human being (Duceppe et al, 2019). Interestingly, Lactobacillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Wastewater treatment plants (WWTPs) have been regarded as the major source of antibiotic-resistant bacteria (ARB) and antibiotic-resistance genes (ARGs) 11,12. Previous studies have reported the isolation of several C. freundii strains from WWTPs 13,14. In our investigation of the ARB and ARGs in WWTPs, we obtained a multidrug-resistant strain of C. freundii .…”
Section: Introductionmentioning
confidence: 99%